2020
DOI: 10.1158/1078-0432.ccr-19-1496
|View full text |Cite
|
Sign up to set email alerts
|

The Proteomic Landscape of Pancreatic Ductal Adenocarcinoma Liver Metastases Identifies Molecular Subtypes and Associations with Clinical Response

Abstract: Purpose: Pancreatic ductal adenocarcinoma (PDAC) is a highly metastatic disease that can be separated into distinct subtypes based on molecular signatures. Identifying PDAC subtype-specific therapeutic vulnerabilities is necessary to develop precision medicine approaches to treat PDAC. Experimental Design: A total of 56 PDAC liver metastases were obtained from the UNMC Rapid Autopsy Program and analyzed with quantitative proteomics. PDAC subtypes were identified by principal component analysis based on protein… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
42
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(44 citation statements)
references
References 50 publications
2
42
0
Order By: Relevance
“…It has been shown to facilitate various aspects of cancer, including sustained proliferation, angiogenesis, invasion, and metastasis. 40,41 A recent study by Law et al 42 used quantitative proteomics to analyze PDAC liver metastases and identified four distinct PDAC microenvironment subtypes, including an inflammatory subtype that did not respond to FOLFIRINOX treatment. This subtype was enriched for proteins related to complement activation and adaptive immune response, among others.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown to facilitate various aspects of cancer, including sustained proliferation, angiogenesis, invasion, and metastasis. 40,41 A recent study by Law et al 42 used quantitative proteomics to analyze PDAC liver metastases and identified four distinct PDAC microenvironment subtypes, including an inflammatory subtype that did not respond to FOLFIRINOX treatment. This subtype was enriched for proteins related to complement activation and adaptive immune response, among others.…”
Section: Discussionmentioning
confidence: 99%
“…These could be used to elucidate the molecular features and underlying pathogenesis of various tumors and contribute to the development of novel treatment strategies. For instance, proteomic profiling of diffuse-type gastric cancer and pancreatic ductal adenocarcinoma with liver metastases revealed their unique molecular signatures that helped develop an optimal treatment strategy ( 7 , 8 ). Similarly, proteomic analysis identified novel therapeutic targets of early-stage hepatocellular carcinoma ( 9 ).…”
mentioning
confidence: 99%
“… 44 , 46 Importantly, patients with basal-like tumors have higher pathologic grades and worse OS compared with those with classical tumors. 44 , 46 , 48 , 50 , 330 Nevertheless, there is no consensus on subtype-specific treatment regimens. Although Collisson et al reported that QM-PDA subtype patients had significantly worse outcomes compared with patients with other subtypes, they found that in pancreatic cancer cells, the QM-PDA subtype was more sensitive to gemcitabine.…”
Section: Clinical Perspectives Of Current Advances In Pancreatic Cancermentioning
confidence: 99%
“… 48 Law et al reported proteomic-based subtyping of pancreatic cancer liver metastases and identified four distinct pancreatic cancer subtypes, i.e., metabolic, progenitor-like, proliferative, and inflammatory. 330 Pancreatic cancer patients with metabolic and progenitor-like subtypes showed significant benefit from FOLFIRINOX treatment.…”
Section: Clinical Perspectives Of Current Advances In Pancreatic Cancermentioning
confidence: 99%